Hypoglycemic effect of Helichrysum odoratissimum in alloxan induced diabetic mice - Njagi, J.M.; Ngugi, Mathew P.; Kibiti, Cromwell M.; Ngeranwa, Joseph; Njue, Wilson N.; Gathumbi, Peter; Njagi, Eliud N. (My University, 2015)
Diabetes mellitus is a disease of antiquity with worrying global incidence and prevalence. Conventional management and/or treatment interventions have been hampered by drawbacks like high costs, inaccessibility, likelihood of potential adverse and toxic effects among others. Use of antidiabetic phytodrugs has been on the rise, particularly in the developing countries, perhaps due to cost implications and accessibility advantages. In this study, an aqueous leaf extract of the medicinal plant Helichrysum odoratissimum was bioscreened for their hypoglycemic potential in alloxan-induced diabetic mice. Three dose ranges were used viz; 50 mg/kgbwt, 100 mg/kgbwt and 150 mg/kgbwt. Results indicate that the extract appreciably lowered blood glucose level in the diabetic mice. The glucose lowering potency of this extract was dose dependent. Preliminary in vivo toxicity assessment revealed that the plant has no discernible toxicity on the major organs of the study animals. The study results confirm the folklore reports from traditional medical practitioners that the extract has safe bioactivity against diabetes mellitus. It avails an impetus for further bioscreening efforts with a view to the development of more hypoglycemic agents in future.
Keywords: Diabetes mellitus; Diabetic mice; In-vivo toxicity; Aqueous leaf extract